2019
DOI: 10.1109/tasc.2019.2898001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field Enhancement of Performance of Superconducting Nanowire Single-Photon Detector

Abstract: We present SNSPDs from NbN nanowires shaped after square-spiral that allows an increase not only in critical currents but also an extension of spectral detection efficiencies by just applying an external magnetic field. Using negative electron-beam lithography with the positive resist for shaping nanowires, made it possible to reduce the inner bend radius. Consequently, the effect of critical-current enhancement in the magnetic field becomes stronger than it was demonstrated earlier. Here we achieved a 13% inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…2 appears to be due to the SNSPD itself. While slight asymmetries in the field-dependent SNSPD response have been reported before for mT-scale perpendicular fields and ascribed to magnetic-field induced currents that oppose current crowding effects at the corners of the meander line [23,25,26], the asymmetries reported here rely on similar bias currents but magnetic fields three orders of magnitude larger. Thus, the previous models for asymmetric SNSPD responses to magnetic fields do not appear to explain this result.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…2 appears to be due to the SNSPD itself. While slight asymmetries in the field-dependent SNSPD response have been reported before for mT-scale perpendicular fields and ascribed to magnetic-field induced currents that oppose current crowding effects at the corners of the meander line [23,25,26], the asymmetries reported here rely on similar bias currents but magnetic fields three orders of magnitude larger. Thus, the previous models for asymmetric SNSPD responses to magnetic fields do not appear to explain this result.…”
supporting
confidence: 71%
“…Early modeling efforts suggested that perpendicular magnetic fields would reduce the critical current for a conventional meander line SNSPD, but small negative perpendicular magnetic fields could increase the critical current of devices patterned in a spiral layout [23]. Other experimental efforts found a slight asymmetry in the dark count rate of TaN and NbN SNSPDs as a function of field [25,26], consistent with previous modeling [23], subject to the assumption that dark counts originate largely at the sharp corners of the device and allowing for some heterogeneity in the device fabrication [25].…”
mentioning
confidence: 99%